2015
DOI: 10.1007/s12517-015-1993-2
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and structural mapping of the Aynak-Logar Valley (eastern Afghanistan) from hyperspectral remote sensing data and aeromagnetic data

Abstract: The Aynak-Logar Valley is located about 30 km south of Kabul in Afghanistan and contains the Aynak copper-cobalt deposit. Satellite remote sensing data obtained from Landsat Enhanced Thematic Mapper (ETM+) and DEM extracted from the Shuttle Radar Topography Mission (SRTM) were used to study the surface geology, while regional aeromagnetic data were used to identify the main magnetic sources in the region. The main magnetic anomaly appeared to originate at a depth of less than 1 km, although the coarse 1-km spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…highly magnetized rocks in ALV). Previous research development in the study area showed that the Aynak region possesses four magnetic anomalies associated with four magnetic sources (Azizi et al, 2015). Figure 14 illustrates the depth to the main magnetized source body which is approximately 1 km, assuming magnetization intensity varies from 1.0 to 3.8 A/m and the sources have a near vertical dip.…”
Section: F I E L D E X a M P L Ementioning
confidence: 94%
See 2 more Smart Citations
“…highly magnetized rocks in ALV). Previous research development in the study area showed that the Aynak region possesses four magnetic anomalies associated with four magnetic sources (Azizi et al, 2015). Figure 14 illustrates the depth to the main magnetized source body which is approximately 1 km, assuming magnetization intensity varies from 1.0 to 3.8 A/m and the sources have a near vertical dip.…”
Section: F I E L D E X a M P L Ementioning
confidence: 94%
“…An airborne magnetic survey for the study area (ALV) was carried out in 2006 and 2008 by the Naval Research Laboratory (NRL) and the USGS (Ashan et al, 2007;Shenwary et al, 2011). Previous geophysical investigation in the study area (Azizi et al, 2015) helped to validate our computer program. The high-amplitude magnetic anomalies associated with various magnetic units have been observed in the area.…”
Section: F I E L D E X a M P L Ementioning
confidence: 99%
See 1 more Smart Citation
“…8. A magnetic survey is a powerful method to study the location of faults and other geological structures (dykes, intrusions) and is routinely applied in mining exploration surveys [6]. The remote-sensing data were processed using Earth Resource (ER) Mapper Ver.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining spectral with other remote sensing data types is increasingly used to enhance mineral mapping performance. Therefore, e.g., Azizi et al [5] combined hyperspectral and aeromagnetic data for mineral and structural mapping, while Bersi et al [6] used multispectral and aerogravity data for the exploration of iron deposits. However, the combination of spectral and geomorphological data is a yet seldom used, but promising approach for the mapping of geomorphologically-prominent deposits.…”
Section: Introductionmentioning
confidence: 99%